Representasi Toxic Relationship Tokoh Aurora Pada Film Jalan Yang Jauh Jangan Lupa Pulang - Ega Arfiansyah; Arif Ardy Wibowo (MAVIS : Jurnal Desain Komunikasi Visual, 2024)
This research aims to describe the representation of the toxic relationship of the character Aurora in the film Jalan Yang Jauh Jangan Lupa Pulang using John Fiske's semiotic analysis method, The Codes of Television theory. This theory has three level classifications, including the reality level, representation level and ideology level. This research uses a qualitative descriptive approach method using observation, documentation and literature study as data collection techniques. The formulation of this research problem is as follows; What is the reality level of Aurora's character's toxic relationship in the film Jalan Yang Jauh Jangan Lupa Pulang? What is the level of representation of Aurora's toxic relationship in the film Jalan Yang Jauh Jangan Lupa Pulang? What is the ideological level of Aurora's toxic relationship in the film Jalan Yang Jauh Jangan Lupa Pulang?. The results of this research describe that the level of reality, level of representation, and level of ideology in the character Aurora have similarities with the current social reality. Where the gestures and expressions of each film actor highlight this side, such as the characteristic of not caring or being indifferent to the existence of people in the surrounding environment, in other words, the egoism side is more prominent in the character of Aurora as a character who experiences a toxic relationship.